GESTÃO E MAPEAMENTO DE PROCESSOS NAS INSTITUIÇÕES PÚBLICAS: UM ESTUDO DE CASO EM UMA UNIVERSIDADE FEDERAL - Maria Teresa Pires Costa (Universidade Federal de Santa Catarina, 2018)
Linking to the theme of modernization in university governance, shows the analysis of the implementation of the management and process mapping at the Directorate of Personnel Management (DAP) in a Federal University in northeastern Brazil who joined the National Public Management Program and bureaucratization (GesPública) in 2009. It was adopted as a general objective to analyze the management and process mapping of said DAP, identifying the possible benefits in improving the quality of the services provided to users. As a method, we carried out a qualitative research, the case study type, whose unit of analysis was the DAP. Data collection consisted of desk research, questionnaires and interviews. Results show that the methods used to manage and process mapping in DAP were built and developed according to the needs of the University having GesPública as a guide and tool for the development of the project which resulted in agility of procedures, reducing the time spent and improved interpersonal communication, so it is suggested method other public institutions.